First detection of fungal diversity associated with Prunus salicina Lindl malformation syndrome - Dan Huang; Po Pu; Xiaosi He; Mingxian Lan; Bang Du; Lixia Zhu; Qian Li; Yongli Yang; Rui Xiang; Longzhang Wang; Guizhen Li; Rongjiao Wang (All Life)
The Chinese deciduous fruit Prunus salicina Lindl is loved by people because of its distinctive flavor and significant industrial worth. This study presents the first report of abnormal leaf bud in Prunus salicina Lindl. Malformation of Prunus salicina Lindl leaf buds leads to abnormal development and growth, causing deformities and a decrease in fruit yield. Identifying the underlying causes and causative pathogens is essential for effective disease management. In this experiment, we observed the Malformation Syndrome in Prunus salicina Lindl and used the internal transcribed spacer (ITS) to compare fungal diversity between malformed and healthy leaf buds. These results show a higher level of fungal diversity in diseased leaf buds. Alternaria, Curvibasidium, Symmetrospora, Fonsecazyma, and other genera among the identified fungi are suspected to induce the malformations. Potential contributors to these malformations include Endophyte-plant_Pathogen and Plant_pathogen-Undefined_saprotroph. These findings provide valuable insights for further research on the etiology of plum bud diseases, identifying potential pathogens, and formulating control strategies.